Doing fieldwork in areas of international intervention : a guide to research in violent and closed contexts - Bliesemann de Guevara, Berit; Bøås, Morten, 1965- (Bristol : Bristol University Press, 2020)
Using detailed insights from those with first-hand experience of conducting research in areas of international intervention and conflict, this handbook provides essential practical guidance for researchers and students embarking on fieldwork in violent, repressive and closed contexts. Contributors detail their own experiences from areas including the Congo, Sudan, Yemen, Bosnia and Herzegovina and Myanmar, inviting readers into their reflections on mistakes and hard-learned lessons. Divided into sections on issues of control and confusion, security and risk, distance and closeness and sex and sensitivity, they look at how to negotiate complex grey areas and raise important questions that intervention researchers need to consider before, during and after their time on the ground.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Humanitarian intervention; Humanitarian intervention -- Fieldwork